ANALISIS EFISIENSI DAN SENSITIVITAS USAHATANI SEMANGKA. (Studi kasus di Desa Pilanganom KecamatanTikung Kabupaten Lamongan). - Hamidah, Emmy (Universitas Islam Darul Ulum, 2016)
This research aims to analyze: (1) Eligibility efisiens iusahatani watermelon in the village of Pilanganom sub-district of Tikung lamongan. (2) the rate of increase in sensitivity to the cost of production, a decrease in production and a decrease in output prices in the village of Pilanganom sub-district of Tikung lamongan. The location of this research was conducted in the village of Pilanganom sub-district of Tikung Lamongan. The data used are the primary data and secondary data. Data analysis is the analysis of the efficiency and the sensivitas analyze the feasibility of (B/C Ratio, NPV, IRR and PP) and analysis of the sensitivity by using the DF 20. The results showed that (1) the farming village of Pilanganom Sub-district in the watermelon Tikung Lamongan deserves to be organised with the Gross value of the B/C Ratio Of 1.40, Net B/C Ratio 4.15, NPV IRR 18,822,985 Rp 35%, (2) the possibility of cost of production goes up 10%, 25% production decrease, or a decrease in output prices 10% farmer plant a watermelon is still in a State of viable and profitable. (3) aspects of the farmer of the climate and precipitation according to plant watermelon. The technical aspect of the majority of farmers are still using simple technology. Aspects of the market even though in terms of sales is not just like any other farming but still decent and still very promising.